Reverse type I core - CuI /shell - CuO: A versatile heterostructure for photoelectrochemical applications. (10th March 2018) - Baran, Tomasz; Visibile, Alberto; Wojtyła, Szymon; Marelli, Marcello; Checchia, Stefano; Scavini, Marco; Malara, Francesco; Naldoni, Alberto; Vertova, Alberto; Rondinini, Sandra; Minguzzi, Alessandro
Abstract: Here we report the synthesis of a core - CuI/shell - CuO nanostructure that depending on the applied potential works as photocathode or photoanode in neutral pH upon visible light irradiation. Under cathodic polarization, this material generates a stable cathodic photocurrent but functions as photoanode when anodic polarization is applied. In this new core-shell structure, the relevant position of the band edge potentials is pH–tunable and does not strictly follow the typical Nernstian dependence as by many semiconductor oxides, opening new directions in the nanoscale design of stable photoelectrodes for solar water splitting. Graphical abstract: Image 1